Influence of Plate Size and Design upon Healing of Ulna-Shortening Osteotomies - Jungwirth-Weinberger, Anna; Borbas, Paul; Schweizer, Andreas; Nagy, Ladislav (Journal of Wrist Surgery, 2016)
Purpose Ulna-shortening osteotomy is one of the most established and most frequent operations in hand surgery. However, bone union is not always achieved and the use of plates implies potential risks and problems. The traditional points of criticism are the duration of bone healing, the incidence of nonunion, and the necessity of hardware removal due to the soft tissue irritation by the plate or the screws. These shortcomings have been addressed by an increasing standardization of the procedure and finally specific instruments and implants. The aim of this retrospective study was to compare a new LCP (locking compression plate) Ulna Osteotomy System 2.7 mm (Synthes, Paoli, PA) with the former 3.5-mm LCDCP (limited-contact dynamic compression plate) (Synthes) regarding consolidation, complications, and rate of plate removal.Methods To investigate the effect of an implant and technique specifically designed for this purpose, we have compared the course of healing and the result in 72 patients who have undergone ulnar shortening osteotomy using general instruments and applying a standard osteosynthesis plate (Synthes, 3.5-mm LCDCP) to a consecutive cohort of 40 patients who had ulnar shortening using the new dedicated ulna-shortening osteotomy system plate (Synthes, 2.7-mm LCP). Clinical and radiologic evaluation was performed 8 weeks, 3 months, 6 months, and 1 year postoperatively in all patients.Results The latter displayed shorter bone healing time, suggesting an advantage of an oblique osteotomy. There was no significant difference in rate of plate removal. Ultimate complication and consolidation rate was not different. Conclusion Using the new LCP 2.7 implant, time to consolidation was shorter and oblique osteotomies healed faster than transverse ones. However, in spite of the smaller plate, screws, and tapered design, the plate did not cause less local problems and failed to decrease the necessity of plate removal. Furthermore, the cost of the implant is higher than the LCDPC 3.5.Type of Study Retrospective comparative study.Therapeutic evidence Level III
Keywords: ulna shortening; osteotomy; osteosynthesis; ulnocarpal impaction